2016
DOI: 10.2134/agronj2015.0427
|View full text |Cite
|
Sign up to set email alerts
|

Iron Filings Cement Engineered Soil Mix

Abstract: Engineered soil mixes are expected to maintain plant growth while minimizing nutrient leaching in greenhouse and bioretention applications. Iron (Fe) has been suggested within plant growth mixtures as a sorbent for phosphorus. The purpose of this study was to determine if Fe filings are an appropriate component of engineered plant growth mixtures. Iron filings were added to engineered soil mixes in laboratory columns, and plants were grown for 2 mo. Unfortunately, Fe filings partially cemented the engineered m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At least for P leaching, sorption to soils in the mixes was adequate in the absence of inorganic non-soil P sorption products. The soils were not harmful to plant growth as sorbent materials could be [6]; however, excess nitrate leaching occurred over time. Overall, it is recommended that bioretention cells and other plant growth media include soil as a component to reduce P leaching.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least for P leaching, sorption to soils in the mixes was adequate in the absence of inorganic non-soil P sorption products. The soils were not harmful to plant growth as sorbent materials could be [6]; however, excess nitrate leaching occurred over time. Overall, it is recommended that bioretention cells and other plant growth media include soil as a component to reduce P leaching.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of biochar and perlite or dolomite (3% by volume) did not retain P [19]. Addition of iron filings (3% by volume) resulted in partial cementation of the sand or soil mixes [6]. Addition of manure compost resulted in unacceptable leaching loss of nitrate [19]; however, layering the compost on top rather than mixing throughout reduced nitrate leaching.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, leaching of Zn was significantly reduced by combining scrap tire rubber with the water treatment residuals. When comparing batch study and column study results for six different amendments, found that column studies were a more realistic test than batch studies when determining removal efficiencies and service lives of amended media Logsdon and Sauer (2016a). published the findings of laboratory studies demonstrating that iron filings were not suitable as soil amendments for engineering media because they caused cementation of the soils.…”
mentioning
confidence: 99%